1992
DOI: 10.1085/jgp.99.6.961
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of G protein beta gamma subunit activation of the muscarinic K+ channel in guinea pig atrial cell membrane. Comparison with the ATP-sensitive K+ channel.

Abstract: A B ST R AC T The mechanism of G protein ~3,/subunit (Gl3v)-induced activation of the muscarinic K + channel (KAch) in the guinea pig atrial cell membrane was examined using the inside-out patch clamp technique. G0v and GTP-~,S-bound ct subunits (G*ds) of pertussis toxin (PT)-sensitive G proteins were purified from bovine brain. Either in the presence or absence of Mg 2+, GI~ ~ activated the KACh channel in a concentration-dependent fashion. 10 nM G~ almost fully activated the channel in 132 of 134 patches (98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
60
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(70 citation statements)
references
References 49 publications
9
60
0
1
Order By: Relevance
“…Preconditioning with either 10 or 60 minutes of reperfusion produced a marked reduction (P<.05) in infarct size (6.7±2.5% and 8.7±2.6%, respectively, versus 26.9±4.3% in controls). Administration of adenosine with a 10-minute drug-free period before 60 minutes of occlusion resulted in a marked decrease in infarct size similar to that seen with preconditioning (9.6±1.7% versus 26.9±4.3% in controls); however, the protection disappeared when a 60-minute drugfree period was allowed after adenosine administration (23 Adenosine is a metabolite of adenine nucleotides; it accumulates quickly in large amounts in the ischemic myocardium.4 A large body of evidence suggests that adenosine can protect the heart against ischemia/reperfusion injury.5 Numerous recent studies have shown that activation of adenosine A, receptors mimicked and blockade of these receptors abolished the effect of ischemic preconditioning to reduce infarct size. 5 Liu and coworkers6 have further demonstrated that in isolated blood-perfused rabbit hearts, intracoronary infusion of adenosine for 5 minutes followed by 10 beats per minute, the heart was paced at that rate with rectangular pulses of 4-millisecond duration and a voltage twice threshold via bipolar electrodes sutured to the left atrial appendage.…”
Section: A Comparison Of Adenosine-induced Cardioprotection and Ischementioning
confidence: 54%
“…Preconditioning with either 10 or 60 minutes of reperfusion produced a marked reduction (P<.05) in infarct size (6.7±2.5% and 8.7±2.6%, respectively, versus 26.9±4.3% in controls). Administration of adenosine with a 10-minute drug-free period before 60 minutes of occlusion resulted in a marked decrease in infarct size similar to that seen with preconditioning (9.6±1.7% versus 26.9±4.3% in controls); however, the protection disappeared when a 60-minute drugfree period was allowed after adenosine administration (23 Adenosine is a metabolite of adenine nucleotides; it accumulates quickly in large amounts in the ischemic myocardium.4 A large body of evidence suggests that adenosine can protect the heart against ischemia/reperfusion injury.5 Numerous recent studies have shown that activation of adenosine A, receptors mimicked and blockade of these receptors abolished the effect of ischemic preconditioning to reduce infarct size. 5 Liu and coworkers6 have further demonstrated that in isolated blood-perfused rabbit hearts, intracoronary infusion of adenosine for 5 minutes followed by 10 beats per minute, the heart was paced at that rate with rectangular pulses of 4-millisecond duration and a voltage twice threshold via bipolar electrodes sutured to the left atrial appendage.…”
Section: A Comparison Of Adenosine-induced Cardioprotection and Ischementioning
confidence: 54%
“…Kirsch et al (16) showed that adenosine activates K ATP channels at reduced [ATP] i via the ␣-subunit of inhibitory G protein (16), in contrast to the G i ␤␥-mediated regulation of acetylcholine-sensitive K ϩ current (13). G protein regulates K ATP by removing [ATP] i -induced inhibition (14,15,36).…”
Section: H492mentioning
confidence: 99%
“…adenosine A 1 receptor activation stimulates K ATP channels via an inhibitory G protein (G* i␣ )-mediated pathway (13,14,16,17,20,36). Recently, the stimulation of PKC has been shown to increase K ATP channel activity in cardiac myocytes (11,23,26).…”
mentioning
confidence: 99%
“…Logothetis et al (1987) showed that fly activated a K+ channel. Although this result was originally controversial, it recently has been confirmed and extended (Ito et al, 1992). Perhaps the most revealing case is control of adenylyl cyclase by Gs.…”
mentioning
confidence: 94%